White matter changes in the perforant path area in patients with amyotrophic lateral sclerosis. (14th May 2019) - Mollink, J.; Hiemstra, M.; Miller, K. L.; Huszar, I. N.; Jenkinson, M.; Raaphorst, J.; Wiesmann, M.; Ansorge, O.; Pallebage‐Gamarallage, M.; van Cappellen van Walsum, A. M.
Abstract : Objective: The aim of this study was to test the hypothesis that white matter degeneration of the perforant path – as part of the Papez circuit – is a key feature of amyotrophic lateral sclerosis (ALS), even in the absence of frontotemporal dementia (FTD) or deposition of pTDP‐43 inclusions in hippocampal granule cells. Methods: We used diffusion Magnetic Resonance Imaging (dMRI), polarized light imaging (PLI) and immunohistochemical analysis of post mortem hippocampus specimens from controls ( n = 5) and ALS patients ( n = 14) to study white matter degeneration in the perforant path. Results: diffusion Magnetic Resonance Imaging demonstrated a decrease in fractional anisotropy ( P = 0.01) and an increase in mean diffusivity ( P = 0.01) in the perforant path in ALS compared to controls. PLI‐myelin density was lower in ALS ( P = 0.05) and correlated with fractional anisotropy ( r = 0.52, P = 0.03). These results were confirmed by immunohistochemistry; both myelin (proteolipid protein, P = 0.03) and neurofilaments (SMI‐312, P = 0.02) were lower in ALS. Two out of the fourteen ALS cases showed pTDP‐43 pathology in the dentate gyrus, but with comparable myelination levels in the perforant path to other ALS cases. Conclusion: We conclude that degeneration of the perforant path occurs in ALS patients and that this may occur before, or independent of, pTDP‐43 aggregation in the dentate gyrus of the hippocampus. Future research should focus on correlating the degree of cognitive decline to the amount of white matter atrophy in the perforant path.